Narrating evil : a postmetaphysical theory of reflective judgment - Lara, María Pía (New directions in critical theory., 2007)
Conceptions of evil have changed dramatically over time, and though humans continue to commit acts of cruelty against one another, today we possess a clearer, more moral way of analyzing them. In Narrating Evil, María Pía Lara explores what has changed in our understanding of evil, why the transformation matters, and how we can learn from this specific historical development. Drawing on Immanuel Kant's and Hannah Arendt's ideas about reflective judgment, Lara argues that narrative plays a key role in helping societies acknowledge their pasts. Particular stories haunt our.